2013
DOI: 10.1017/s1368980013002772
|View full text |Cite
|
Sign up to set email alerts
|

Finnish Children Healthy Eating Index (FCHEI) and its associations with family and child characteristics in pre-school children

Abstract: Objective: The objective was to develop a Finnish Children Healthy Eating Index (FCHEI), to determine the relative validity of the index and to examine associations between the index and familial sociodemographic and lifestyle characteristics. Design: Cross-sectional samples of children participating in a population-based birth cohort study in Finland. Setting: Type I Diabetes Prediction and Prevention (DIPP) Study cohort. Subjects: Three-day food records from 1-year-old (n 455), 3-year-old (n 471) and 6-year-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
60
3

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(70 citation statements)
references
References 39 publications
7
60
3
Order By: Relevance
“…Like previous studies, we show that maternal diet (7,12,13) , but not physical exercise (14) , is associated with early childhood diet, and we confirm univariable associations of maternal smoking with unhealthier diets (11) and of maternal non-smoking with healthier diets (7,10) . However, our multivariable findings differ from previous studies indicating that parental alcohol consumption and smoking predict child diet (6)(7)(8)(9)(10)(11) . Ref.…”
Section: Strengths and Weaknesses In Relation To Other Studiescontrasting
confidence: 99%
See 1 more Smart Citation
“…Like previous studies, we show that maternal diet (7,12,13) , but not physical exercise (14) , is associated with early childhood diet, and we confirm univariable associations of maternal smoking with unhealthier diets (11) and of maternal non-smoking with healthier diets (7,10) . However, our multivariable findings differ from previous studies indicating that parental alcohol consumption and smoking predict child diet (6)(7)(8)(9)(10)(11) . Ref.…”
Section: Strengths and Weaknesses In Relation To Other Studiescontrasting
confidence: 99%
“…Compared with previous research (7)(8)(9)(11)(12)(13)(14) , our study provides a broader view over a longer time horizon of how multiple health behaviours from both parents are associated with dietary trajectories throughout childhood and adolescence. Like previous studies, we show that maternal diet (7,12,13) , but not physical exercise (14) , is associated with early childhood diet, and we confirm univariable associations of maternal smoking with unhealthier diets (11) and of maternal non-smoking with healthier diets (7,10) .…”
Section: Strengths and Weaknesses In Relation To Other Studiesmentioning
confidence: 86%
“…The Chinese Children Dietary Index score was observed to be related not only to the foods/food groups and nutrients incorporated into the index, but also to other essential nutrients, such as protein, calcium, magnesium, potassium, vitamin C, vitamin E, and riboflavin. These correlation coefficients were consistent with diet indices developed for children in western countries 8,16,24 and in Indian girls who were vegetarian. 33 These results revealed that the Chinese Children Dietary Index can be used as a valuable SSB¼sugar-sweetened beverage.…”
Section: Discussionsupporting
confidence: 85%
“…Germany (0 to 17 years), [19][20][21][22][23] Finland (1 to 6 years), 24 Spain (2 to 24 years), [25][26][27] and Canada (older than 3 years). 28,29 A few dietary indices measured diet quality among children in Asian countries.…”
mentioning
confidence: 99%
“…To examine if there is substantial group difference between children skilled in mental abacus and their peers on non-symbolic number sense, some important cognitive factors would be controlled. The factors included general intelligence (Cowan & Powell, 2014;Fuchs, Fuchs, Compton, Hamlett, & Wang, 2015;Jordan et al, 2013), visuospatial processing ability (Boonen, van Wesel, Jolles, & van der Schoot, 2014;Kyttala et al, 2014;Looi et al, 2017;Swanson, Jerman, & Zheng, 2009), processing speed (Berg, 2008;Bull & Johnston, 1997;Fuchs et al, 2006), and language processing (Hecht, Torgesen, Wagner, & Rashotte, 2001;Purpura & Ganley, 2014;Wei, Yuan, Chen, & Zhou, 2012). It is to ensure that group difference in approximate number sense originates from mental abacus experience rather than outperformances of the cognitive factors.…”
Section: Introductionmentioning
confidence: 99%